Pengaruh Penggunaan ATLAS, Computer Self-Efficacy, Kompetensi, dan Profesionalisme terhadap Kinerja Auditor - Miranda, Gita; Kurniawati, Indah (https://jurnal.binamandiri.ac.id/, 2024)
Auditor performance is an assessment of the effectiveness and efficiency of an auditor in carrying out their duties. Good auditor performance indicates that the auditor can ensure the reliability of financial statements and provide recommendations that are useful for decision making for information users. This research aims to analyze the effect of using the Audit Tool and Linked Archive System (ATLAS), computer self-efficacy, competence, and professionalism on auditor performance. This research uses a quantitative approach with primary data collection through questionnaires. The sample in this study were 45 respondents selected using purposive sampling technique, with a focus on auditors in Yogyakarta. The results indicated that the use of ATLAS, computer self-efficacy, competence, and professionalism have a significant effect on auditor performance. Auditors with high computer self-efficacy, good competence, high professionalism, and using ATLAS in their work process shows good performance.